2023
DOI: 10.1177/20420188231207544
|View full text |Cite
|
Sign up to set email alerts
|

Pheochromocytoma: a changing perspective and current concepts

Andreas Kiriakopoulos,
Periklis Giannakis,
Evangelos Menenakos

Abstract: This article aims to review current concepts in diagnosing and managing pheochromocytoma and paraganglioma (PPGL). Personalized genetic testing is vital, as 40–60% of tumors are linked to a known mutation. Tumor DNA should be sampled first. Next-generation sequencing is the best and most cost-effective choice and also helps with the expansion of current knowledge. Recent advancements have also led to the increased incorporation of regulatory RNA, metabolome markers, and the NETest in PPGL workup. PPGL presenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 158 publications
(402 reference statements)
0
3
0
Order By: Relevance
“…Neuroblastoma is a pediatric cancer originating from the sympathetic nervous system, often characterized by metastasis and recurrence, and is often inoperable in many instances [ 28 , 29 ]. Pheochromocytomas and paragangliomas are rare neuroendocrine tumors (NETs) associated with a relatively high incidence of local invasion or metastasis, rendering some cases unsuitable for surgical intervention [ 30 , 31 ]. Most of these tumors express high levels of NE transporters [ 28 , 32 ].…”
Section: Radiolabeled Compounds For Norepinephrine (Ne) Transporter-e...mentioning
confidence: 99%
“…Neuroblastoma is a pediatric cancer originating from the sympathetic nervous system, often characterized by metastasis and recurrence, and is often inoperable in many instances [ 28 , 29 ]. Pheochromocytomas and paragangliomas are rare neuroendocrine tumors (NETs) associated with a relatively high incidence of local invasion or metastasis, rendering some cases unsuitable for surgical intervention [ 30 , 31 ]. Most of these tumors express high levels of NE transporters [ 28 , 32 ].…”
Section: Radiolabeled Compounds For Norepinephrine (Ne) Transporter-e...mentioning
confidence: 99%
“…Accordingly, a recent study showed that 78% of pheochromocytomas with atypical anatomical imaging features (on CT or MRI) were totally or predominantly cystic [42]. In this situation, the most accurate way to assess these lesions is using a variety of functional imaging modalities like iodine metaiodobenzylguanidine (MIBG) scintigraphy, 18 fluoro (F) deoxyglucose (FDG) positron emission tomography/computed tomography (PET/CT), 18 FDG-PET/MRI, 18 F-Fluoro-dihydroxyphenylalanine ( 18 F-DOPA) PET/CT, and somatostatin receptor (SSTR) agonist-based PET/CT imaging [42,43]. It was demonstrated that even completely cystic pheochromocytomas captivate radiotracers like MIBG and FDG in the peripheral tumour rim or in residual tumour tissue [42].…”
Section: Question 4: Which Adrenal Cyst Subtypes Exist?mentioning
confidence: 99%
“…Among the clinical symptoms mentioned above, high blood pressure is the classic clinical clue for PPGL 4 . Approximately 65-80% of PPGL patients suffer from hypertension 5 . Surgical resection of PPGL combined with a preoperative combination of α-blockers is an effective treatment option for PPGL 6 .…”
Section: Introductionmentioning
confidence: 99%